Busting for change: a care pathway for overactive bladder. Issue 4 (19th July 2022) - Kovacic, James; Chung, Amanda
Abstract : Overactive bladder is common, underdiagnosed and undertreated. It is challenging to manage but evidence‐based guidelines provide a pathway to effective treatments that will help people with the disease.